Social representations and emergent practices of clients attending casinos in Merida, Yucatan (REVISTA NODO, 2014)
As part of the growing economy of the tertiary sector, throughout the last decade the people of Merida, Yucatan,have noted the proliferation of gambling houses that introduced slots machines, number games and sports betting, among other attractions.However, despite the fact that the state of Yucatan has the lowest wages in the country, the social acceptance of casinos among the people of Merida as an urban recreation alternative is quite high. That led us to think that beyond economic factors, such establishments must provide incentives and other satisfactions that explain their lure to consumers, and that the study of social representations on casinos should provide valuable information for understanding the reasons behind their use. This paper studies the social representations about casinos in 20 people attending them, with information gathered by conducting semi-structured interviews and collecting personal experience narratives. The results split into three sections: 1) Going to the casino, which describes the different conceptions of these establishments, as well as game strategies used by consumers; 2) What others think about my gambling, depicting various comments and opinions of family members and friends about casino customers; and 3) New social practices and behavior, in which both are described, discussed and analyzed in the context of Merida urban dynamics.
Keywords: Casinos; gambling; clients; social practices and representations